2007
DOI: 10.1002/ar.20508
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory muscles of the great‐gray kangaroo (Macropus giganteus)

Abstract: The great-gray kangaroo (Macropus giganteus) belongs to the Diprotodontia suborder (herbivorous marsupials of Australia) of the order of marsupials. We dissected the masticatory muscles in the great-gray kangaroo and classified them based on their innervation. Three (two male and one female) adult great-gray kangaroos (M. giganteus), fixed with 10% formalin, were examined. The masseter muscle of the great-gray kangaroo was classified into four layers (superficial layers 1, 2, 3, and a deep layer), all innervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…In kangaroos and wombats the superficial masseter is usually depicted as having two or more parts (Abbie, 1939; Crompton et al, 2008; Tomo et al, 2007). In kangaroos the more superficial layer originates from the small ventral tip of the masseteric process and inserts on the postero-ventral surface of the inflected mandibular angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In kangaroos and wombats the superficial masseter is usually depicted as having two or more parts (Abbie, 1939; Crompton et al, 2008; Tomo et al, 2007). In kangaroos the more superficial layer originates from the small ventral tip of the masseteric process and inserts on the postero-ventral surface of the inflected mandibular angle.…”
Section: Resultsmentioning
confidence: 99%
“…The terminology used here was selected for its consistency with jaw muscle nomenclature used for marsupials (Abbie, 1939; Crompton et al, 2008; Davison & Young, 1990; Murray, 1998; Tomo et al, 2007; Turnbull, 1970; Warburton, 2009). The masseter muscle group includes three portions (superficial, deep and zygomaticomandibularis) based on their area of origin.…”
Section: Methodsmentioning
confidence: 99%
“…While much attention has been paid to the anatomical diversification of jaw bones and cartilages, few studies have identified developmental mechanisms that provide species- specific pattern to the closely associated musculature. Because the muscles that attach to the upper and lower portions of the jaw skeleton are integral for respiration and feeding, they have undergone dramatic evolutionary change in conjunction with the adaptive radiations of vertebrates (Bemis and Northcutt, 1991; Bowman, 1961; Cabuy et al, 1999; Edgeworth, 1935; Gosline, 1986; Haas, 2001; Holliday and Witmer, 2007; Smith, 1993; Tomo et al, 2007; Turnbull, 1970; Wood, 1965). For example, in groups such as pufferfish (Friel and Wainwright, 1997) and parrots (Toki*ta, 2004; Zusi, 1993), the number and organization of jaw muscles have been extremely modified, reflecting a high degree of plasticity in the developmental programs of the first (i.e., mandibular) arch (Schneider, 2005; Smith and Schneider, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Each muscle group was modelled with two or three subdivisions based on published studies of marsupial jaw muscles (Turnbull, ; Murray, ; Tomo et al. ; Crompton et al. ; Warburton, ; Sharp, ; Sharp & Trusler, ).…”
Section: Methodsmentioning
confidence: 99%